PENGARUH HUMAN CAPITAL, STRUCTURE CAPITAL, DAN PHYSICAL CAPITAL TERHADAP KINERJA PERUSAHAAN PERBANKAN DI INDONESIA - Agustinus Jeneo (Universitas Mercu Buana, 2017)
The objective of this study are to analyze the impact of intellectual capital (HumanCapital, Structure Capital and Physical Capital) on company’s financial performance Return on Assets (ROA) dan Return On Equity (ROE). This research used banking company data that listed in Indonesia Stock Exchange (IDX) 2011-2012. The model that used to measure intellectual capital was Pulic model agregatly-using Value Added Intellectual Coefficient (VAIC™) or separately-using Human Capital Efficiency (HCE), Structure Capital Efficiency (SCE), and Physical Capital/ Capital Employed Efficiency (CEE). The result show: (1) Human Capital Efficiency (HCE) not significant impact on ROA, (2) Human Capital Efficiency (HCE) not significant impact on ROE, (3) Structure Capital Efficiency (SCE) not significant impact on ROA, (4) Structure Capital Efficiency (SCE) negative impact on ROE (5) Physical Capital/Capital Employed Efficiency (CEE) has a positive significant impact on ROA, (6) Physical Capital/Capital Employed Efficiency (CEE) has a positive significant impact on ROE